The use of social media inside and outside the classroom to enhance students’ engagement in EFL contexts - Wang, Hui; Wang, Minqi; Li, Guang (Frontiers in Psychology, 2022)
It could be claimed that without any doubt the Internet has revolutionized the educational system to a great extent. Even though some are still interested in traditional ways of teaching and learning and also face-to-face classes, technological advances, in particular, social media has changed the EFL contexts in a way that will not be compatible with any other methods that have long been utilized before. Despite the fact that some studies have been conducted in different learning contexts, to the researcher’s best knowledge, attention has not been focused on the importance of social media inside and outside the classroom on EFL students’ indulgence. Therefore, the aim of this study is to review the findings of the previous studies to highlight the role of social media in EFL students’ engagement. To reach this goal, this review study first discusses the impact of social media on engagement, then engagement and its classifications are dealt with. Next, the relationship between using social media and students’ engagement is discussed. And finally, some implications are proposed.